2016
DOI: 10.1111/1753-0407.12426
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of insulin intensification strategies with insulin lispro low mixture twice daily versus basal insulin glargine and prandial insulin lispro once daily in East Asian and Caucasian patients with type 2 diabetes mellitus

Abstract: Both strategies improved glycemic control in a small group of EA and Caucasian patients not adequately controlled on insulin glargine plus metformin and/or pioglitazone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…In all of these studies, the change from baseline in HbA1c was, in general, not significantly different between the premixed insulin analog and basal–bolus groups, with one study showing non‐inferiority on the basis of this comparison. Another showed a significantly greater decrease in HbA1c in the premixed insulin analog group compared with the basal–bolus group . Likewise, other outcomes, including the incidence of hypoglycemia and weight/BMI gain, were not significantly different between groups (or favored the premixed insulin analog group), except in the study reported by Hirao et al ,.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…In all of these studies, the change from baseline in HbA1c was, in general, not significantly different between the premixed insulin analog and basal–bolus groups, with one study showing non‐inferiority on the basis of this comparison. Another showed a significantly greater decrease in HbA1c in the premixed insulin analog group compared with the basal–bolus group . Likewise, other outcomes, including the incidence of hypoglycemia and weight/BMI gain, were not significantly different between groups (or favored the premixed insulin analog group), except in the study reported by Hirao et al ,.…”
Section: Resultsmentioning
confidence: 91%
“…Of these #bib165 were duplicates and 356 were excluded. Three additional studies were identified (including two that had been submitted, but not published at the time of the literature search); hence 18 studies from the literature were included in the review. Three eligible studies were identified in the search of ClinicalTrials.gov and included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations